Study on Volatile Constituents, Cytotoxic Activity and Antioxidant Potential of Fixed Extracts of Copaifera luetzelburgii Harms - Sidney Goncalo de Lima; Juliana de Sousa Figueredo; Marcelo Costa dos Santos; Allan Kayk Sales Meneses; Marcio dos Santos Rocha; José Galberto Martins da Costa; Rozeverter Moreno Fernandes (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Copaibas (Leguminosae - Caesalpinoideae) are native to the tropical region of Latin America and also West Africa. Their stem barks are used in folk medicine as a cicatrizing, anti-inflammatory, antiseptic, and antitumor agent. Thus, a phytochemical investigation of both the qualitative and quantitative chemical composition of the volatile and fixed constituents of the leaves, and bark of the Copaifera luetzelburgii stem is necessary and evaluated for their cytotoxicity, antioxidant potential and total phenol content. In this study, we aimed to evaluate the chemical composition of the volatile constituents, the cytotoxic activity, and the antioxidant potential against DPPH and ABTS radicals of C. luetzelburgii Harms, widely distributed in the Quilombola Community, municipality of Sao Miguel do Tapuio, State of Piauí, Brazil. The volatile constituents were extracted by the hydrodistillation method and analyzed by GC-MS. The ethanolic stem extract (EECC) was also analyzed by LC-ESI-TOF-MS. The phytochemical screening of the leaf and stem bark extracts (SBE) was performed, with the SBE showing more promising results. While germacrene D (27.12%), \(β\)-caryophilylene (16.43%), and germacrene B (12.58%) were found to be the major constituents in the essential oil from leaves (EOL); \(γ\)-selinene (26.79%), 7-epi-\(α\)-selinene (24.73%) and \(β\)-selinene (14.63%) were the major constituents in the oil of the stem bark. Toxicity evaluation was performed in Artemia salina with results considered inactive (LC50 >1000\(μ\)g mL-1). The EECC showed the best of total phenols contents 31.41 ± 3.07, as, for antioxidant activity performed against the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) with CE50 value = 40.11 ± 2.31, while the ethanolic extract of copaiba leaves (EEFC) with CE50 value = 74.13 ± 6.05, all ready for the test 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) EECC showed better potential compared to EEFC. Thus, we hope that this work can contribute significantly to new research related to the species in phytochemistry and pharmacology.